Assessing urban waterfront public space service quality using importance performance analysis (IPA) - Suminar, Lintang; Ramadhani, Difa Ayu Balqist; Endriyanto, Dhimas (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The urge for urban public space evolved in increasingly dense cities. Tirtonadi Dam Park is a waterfront-designed urban park located on Bengawan Solo riverbank area. To support the activities, adequate infrastructure must be provided. The objective of this study was to assess Tirtonadi Dam Park's service quality as an urban public space and suggest methods to improve it to promote local communities' economic development. The variables—infrastructure, access & linkage, comfort & images, use & activity—were evaluated and compiled into 16 indicators. Based on user perceptions, Importance Performance Analysis (IPA) was employed to determine the performance and importance levels of predetermined variables. The findings demonstrated that vegetation, infrastructure for the disabled, and drainage and water systems all dropped into the